The Mediating Role of Psychological Capital: Perceived Organizational Support and Well-Being - Hati, Putri Seni; Syahrizal, Syahrizal (Human Resource Management Studies, 2023)
This article was written to analyze the influence of the impact of perceived organizational support on employee well-being of West Sumatra Province Transportation Service employees. 68 employees of the West Sumatra Province Transportation Service were respondents in this research. Data were statistically analyzed using SEMPLS structural equation modeling. Research result show that: (1) perceived organizational support has a positive and significant impact on well-being in employees of the West Sumatra Province Transportation Service (2) perceived organizational support has a positive and significant impact on psychological capital in employees of the West Sumatra Province Transportation Service (3) psychological capital has a positive impact and significantly on well-being in employees of the West Sumatra Province Transportation Service (4) psychological capital has a positive and significant mediating impact on the influence of perceived organizational support on well-being in employees of the West Sumatra Province Transportation Service.